Analisis Penentuan Core Business Pada Masterplan Kawasan Ekonomi Khusus Mekar Putih di Kabupaten Kotabaru - Muhammad, Fadel; Effendi, Muhammad (PPJP ULM, 2019)
This study aims to (1) determine what factors are considered in determining theCore Business in the Mekar Putih Special Economic Zone Masterplan in KotabaruRegency, (2) To determine perceptions of government, private sector. The community inthe Core Business choice of the Mekar Putih Special Economic Consultation Masterplanin Kotabaru Regency, (3) To analyze what Core Business is suitable to be developed inthe Mekar Putih Special Economic Zone Masterplan in Kotabaru District.Respondents in this study were five respondents from local government, fiverespondents from the private sector, 14 respondents from community leaders andinstitutions, and 95 respondents from the community. The method used in processing datais the AHP (Analytical Hierarchy Process) method. and Descriptive QuantitativeThe results of this study indicate that the choice of regional government for CoreBusiness in the Mekar Putih Special Economic Zone Master Plan is the Core BusinessIndustri 67% and Tourism Core Business 33%, and the choice of private parties for CoreBusiness in the Mekar Putih Special Economic Zone Masterplan Business Industri 80%and Core Business Tourism 20%, for community leaders and community institutions forthe determination of Core Business in the Mekar Putih Special Economic ZoneMasterplan, is the 57% Core Business Industri and 43% Core Business Tourism and thegeneral public in determining Core Business is Core Business Industri 81% and TourismCore Business 19% With the most dominant conclusion is Industrial Core Business whichis the main activity in the White Blooms Special Economic Zone.